Beurteilung der Fischbestände in Nordatlantik, Nord- und Ostsee. Einschätzung durch den Internationalen Rat für Meeresforschung vom Mai 1999 - Hammer, Cornelius (1999)
The spring session of ACFM gave advice for a number of stocks in the North Atlantic, North Sea and Baltic. The situation is given here for stocks of higher importance for the German fishery. These are: Blue Whiting: A short term upwards trend is observed, which, however, will not last very long, due to too intense fishing. Cod in Kattegat: Stock is outside safe biological limits. No immediate recovery in sight. Cod in Sub. Div. 22– 24 (Baltic): Stock is outside safe biological limits. Due to weak recruitment not immediate recovery in prospect. Greenland Halibut: Stock outside safe biological limits and still in downward trend. Herring (atlanto-scandian, Norw. spring spawner): Stock inside safe biological limits, weak recruitment of the past 5 years will, however, lead to a reduction of the biomass. Redfish: Generally decreasing tendency observed, a reduction of the fishery is recommended.